Coagulation in Lymphatic System - Zhang, Wendi; Li, Jiang; Liang, Jiangjiu; Qi, Xiumei; Tian, Jinghui; Liu, Ju (Frontiers in Cardiovascular Medicine, 2021)
The lymphatic system maintains homeostasis of the internal environment between the cells in tissues and the blood circulation. The coagulation state of lymph is determined by conditions of coagulation factors and lymphatic vessels. Internal obliteration, external compression or abnormally increased lymphatic pressure may predispose to localized lymphatic coagulation. In physiological conditions, an imbalance of antithrombin and thrombokinase reduces lymphatic thrombosis. However, the release of factor X by lymphatic endothelium injury may trigger coagulation casacade, causing blockage of lymphatic vessels and lymphedema. Heterogeneity of lymphatic vessels in various tissues may lead to distinct levels and patterns of coagulation in specific lymphatic vessels. The quantitative and qualitative measurement of clotting characteristic reveals longer time for clotting to occur in the lymph than in the blood. Cancer, infections, amyloidosis and lymph node dissection may trigger thrombosis in the lymphatic vessels. In contrast to venous or arterial thrombosis, lymphatic thrombosis has rarely been reported, and its actual prevalence is likely underestimated. In this review, we summarize the mechanisms of coagulation in lymphatic system, and discuss the lymphatic thrombosis-related diseases.